A negative-bias-temperature-instability study on omega-gate silicon nanowire SOI pMOSFETs - Silva, Vanessa C. P.; Wirth, Gilson I.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The Negative-Bias-Temperature-Instability (NBTI) is an important reliability parameter for advanced technology nodes. This work presents an experimental study of NBTI in omega-gate nanowire (NW) pMOSFET. The 3D-numerical simulations were performed in order to better understand the NBTI effect in NW transistors. The results shows that NBTI in NW is high (Δ VT≈200-300mV-for W = 10nm) due to the higher gate oxide electric field accelerating the NBTI effect providing a higher degradation. This study was performed for different channel widths and lengths.
Keywords: MOSFET; NBTI; NW; SOI